2011
DOI: 10.1038/gt.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Successful attenuation of humoral immunity to viral capsid and transgenic protein following AAV-mediated gene transfer with a non-depleting CD4 antibody and cyclosporine

Abstract: The ability of transient immunosuppression with a combination of a non-depleting anti-CD4 (NDCD4) antibody and cyclosporine (CyA) to abrogate immune reactivity to both adeno-associated viral vector (AAV) and its transgene product was evaluated. This combination of immunosuppressants resulted in a 20-fold reduction in the resulting anti-AAV8 antibody titres, to levels in naïve mice, following intravenous administration of 2Â10 12 AAV8 vector particles per kg to immunocompetent mice. This allowed efficient trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…In parallel, and besides the fact that a single injection could provide sustained human GNE expression for a long period of time, improving the capacity of AAV8 to avoid as much as possible an immunogenic response could ensure a reuse of the virus if needed. Recent studies show much advancement toward this goal, by either modulating the viral capsid structure to obtain more specific cell targeted infection [26], or by immunosuppression [27]. Recently it has been estimated that the frequency of anti AAV8 antibodies in the population is about 15% [28], thus patients potentially eligible for such a therapy should be screened for the presence of those antibodies before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, and besides the fact that a single injection could provide sustained human GNE expression for a long period of time, improving the capacity of AAV8 to avoid as much as possible an immunogenic response could ensure a reuse of the virus if needed. Recent studies show much advancement toward this goal, by either modulating the viral capsid structure to obtain more specific cell targeted infection [26], or by immunosuppression [27]. Recently it has been estimated that the frequency of anti AAV8 antibodies in the population is about 15% [28], thus patients potentially eligible for such a therapy should be screened for the presence of those antibodies before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…108,112 Subsequent efforts to implement successful gene therapy trials aim at increasing transgene expression by means of diminishing host immune responses. [116][117][118] However, laboratory mice did not reproduce T cell-mediated destruction of AAVtransduced hepatocytes. AAV capsid-specific memory CD8 + T cells can recognize their cognate antigen and mount a proliferative response, 119 but they fail to reduce the expression of the transgene encoded by the rAAV.…”
Section: B Adaptive Immune Response To Raav Vectorsmentioning
confidence: 91%
“…Since NHP are naturally infected with AAVs, studies in macaques have facilitated modeling the effects of pre-existing immunity on rAAV gene transfer. Several studies in NHP analyzed the feasibility of AAV or adenovirus-mediated gene transfer under the effects of transient pharmacological immunosuppressive regimens designed to block T-cell mediated adaptive immune responses [116][117][118][120][121][122] (Table 4). However, a report by Li et al 119 concluded that studies in NHP fail to model the destruction of transduced hepatocytes by capsid-specific CTLs as it occurs in humans.…”
Section: B Adaptive Immune Response To Raav Vectorsmentioning
confidence: 99%
“…The ligation products were transferred to appropriately prepared bacterial competent cells; positive clones were identified by PCR and sequenced. Construction of lentiviral vectors was carried out as previously described (McIntosh et al, 2012).…”
Section: Construction Of Cyclophilin Bsirna Lentiviral Vectormentioning
confidence: 99%